2011
DOI: 10.1038/aps.2011.96
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of angiotensin-(1–7) and angiotensin II type 1 receptor by telmisartan and losartan in adriamycin-induced rat heart failure

Abstract: Aim:To investigate the possible effects of telmisartan and losartan on cardiac function in adriamycin (ADR)-induced heart failure in rats, and to explore the changes in plasma level of angiotensin-(1-7)[Ang-(1-7)] and myocardial expression of angiotensin II type 1/2 receptors (AT 1 R / AT 2 R) and Mas receptor caused by the two drugs. Methods: Male Sprague-Dawley rats were randomly divided into 4 groups: the control group, ADR-treated heart failure group (ADR-HF), telmisartan plus ADR-treated group (Tel+ADR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…Moreover, Losartan also increased renal expression of ACE2, the main responsible for Ang-(1–7) synthesis at renal tissue [53]. Corroborating the present data, previous studies reported similar effects of ARBs on the modulation of ACE2Ang-(1–7)/Mas receptor axis at different sites [54][58]. In this regard, Ferrario et al (2005) showed that Losartan increases plasma and urinary levels of Ang-(1–7) and renal ACE2 activity, without changing the expression of Mas receptor, AT 1 or ACE in Lewis rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, Losartan also increased renal expression of ACE2, the main responsible for Ang-(1–7) synthesis at renal tissue [53]. Corroborating the present data, previous studies reported similar effects of ARBs on the modulation of ACE2Ang-(1–7)/Mas receptor axis at different sites [54][58]. In this regard, Ferrario et al (2005) showed that Losartan increases plasma and urinary levels of Ang-(1–7) and renal ACE2 activity, without changing the expression of Mas receptor, AT 1 or ACE in Lewis rats.…”
Section: Discussionsupporting
confidence: 90%
“…Igase et al (2011) in a model of hypertensive nephropathy showed that olmesartan treatment increased plasma levels of Ang-(1–7) leading to cardiprotective and renoprotective effects [55]. In a model of ADR-induced heart failure in Male Sprague-Dawley rats, Zong et al (2011) detected a decrease of plasma Ang-(1–7) levels and reduced myocardial expression of Mas receptor, while the treatment with telmisartan or losartan increased Ang-(1–7) levels and suppressed myocardial AT 1 receptor expression without changing the expression of Mas [58]. Recent studies of Sukumaran et al (2011 and 2012) showed that the protein and mRNA levels of Mas receptor, ACE2 and Ang-(1–7) were upregulated in olmesartan treated group in experimental autoimmune myocarditis and these changes in RAS components decreased the expression of inflammatory markers [56], [57].…”
Section: Discussionmentioning
confidence: 99%
“…This notion is further emphasized by the recent discovery of MrgD as another novel receptor for Ang- (1-7) regulating the physiological arterial pressure. 9 Physiological relevance of the Ang-(1-7)/AT1-R axis could be, however, questioned given that the affinity/potency of Ang-(1-7) for AT1-R is modest (≈300 nmol/L) and relatively far from plasma concentrations generally described, with significant differences in between rodents (nmol/L) 26,27 or human species (pM). [28][29][30] Nevertheless, despite the RAAS was originally described as a circulating system, it is now widely accepted that a distinct local RAAS does exist in several tissues, 31 thus promoting a close ligand-receptor proximity to ensure an accurate spatiotemporal regulation of RAAS actions similar to that observed for neurotransmitters concentrations in the synaptic cleft after release.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, losartan treatment protected skeletal muscle against disuse atrophy . Interestingly, several studies have demonstrated that ACEi or ARB treatments not only inhibit ACE or AT‐1 blockade, respectively, but also increase Ang (1–7) levels, probably by an attenuation of its degradation (see Fig. ).…”
Section: Contribution Of Ras Axis To Muscle Pathologiesmentioning
confidence: 94%